Influence of pH on the Properties of Chemical Bath Deposited Ni4S3 Thin Films (Bangladesh Journal of Scientific and Industrial Research, 2011)
The Ni4S3 thin films were prepared by chemical bath deposition method. The chemical bath contained nickel sulphate and sodium thiosulfate which supplied the Ni2+ and S2- ions, respectively. The structure and morphology of the films were studied using X-ray diffraction and atomic force microscopy technique, respectively. Absorbance spectra data of the films were obtained by UV-Vis spectrophotometer. The influence of pH was investigated in order to determine the best conditions for deposition process. The number of peaks attributable to cubic structure of Ni4S3 increased to three as the pH was increased to 2.5 according to XRD analysis. In optical absorption spectra, we found that the highest absorbance value was obtained for the films deposited at pH 2.5. Also, the AFM image revealed that the films were smooth, compact and uniform at this pH value. The band gap of films ranged from 0.85 to 1.8 eV depending upon the pH value. Key words: Nickel sulphide; Thin films; Solar cells; Semiconductor. DOI: http://dx.doi.org/10.3329/bjsir.v46i2.8192 Bangladesh J. Sci. Ind. Res. 46(2), 243-246, 2011